Expression of Human Tissue Factor Pathway Inhibitor on Vascular Smooth Muscle Cells Inhibits Secretion of Macrophage Migration Inhibitory Factor and Attenuates Atherosclerosis in ApoE−/− Mice. Issue 15 (14th April 2015) - Chen, Daxin; Xia, Min; Hayford, Claudia; Tham, El-Li; Semik, Vikki; Hurst, Stuart; Chen, Ying; Tam, Henry H.; Pan, Jun; Wang, Yucheng; Tan, Xiaojin; Lan, Hui-Yao; et al.
<x xml:space="preserve">Abstract</x> Background— Tissue factor (TF) and coagulation proteases are involved in promoting atherosclerosis, but the molecular and cellular bases for their involvement are unknown. Methods and Results— We generated a new strain (ApX4) of apolipoprotein E–deficient mice expressing a membrane-tethered human tissue factor pathway inhibitor fusion protein on smooth muscle actin–positive cells, including vascular smooth muscle cells (SMCs). ApX4 mice developed little atherosclerosis on either a normal chow or high-fat diet. Lipid levels were similar to those in parental ApoE−/− mice, and there was no detectable difference in systemic (circulating) tissue factor pathway inhibitor levels or activity. The small lipid-rich lesions that developed had markedly reduced leukocyte infiltrates, and in contrast to ApoE−/− mice, SMCs did not express macrophage migratory inhibitory factor (MIF), including at sites distant from atheromatous lesions. Low levels of circulating MIF in ApX4 mice normalized to levels seen in ApoE−/− mice after injection of an inhibitory anti–human tissue factor pathway inhibitor antibody, which also led to MIF expression by tissue factor–positive medial SMCs. MIF production by SMCs in ApoE−/− mice in vitro and in vivo was shown to be dependent on tissue factor and protease-activated receptor signaling, which were inhibited in ApX4 mice. Conclusions— Our data indicate that tissue factor plays a hitherto unreported role in the generation of MIF by SMCs in atherosclerosis-prone ApoE−/− mice, inhibition of which significantly prevents the development of atherosclerosis, through inhibition of leukocyte recruitment. These data significantly enhance our understanding of the pathophysiology of this important pathology and suggest new potential translational strategies to prevent atheroma formation.